Innovative Design and Implementation of Portable and Rechargeable Air Purifier and Humidifier - Ukagwu, Kelechi John; Enzoionzi, Azando Isaac; Eze, Val Hyginus Udoka; Uche, Chikadibia Kalu Awa; Ukagwu, Faith (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
This study presents the innovative design and successful implementation of a Portable and Rechargeable Air Purifier and Humidifier (PRAPH) aimed at addressing indoor air quality issues in Uganda. The device combines air purification and humidification functionalities into a compact, user-friendly, and energy-efficient unit. The design phase of the PRA-PH involved a thorough analysis of existing air purifiers and humidifiers, identifying key limitations such as limited portability, energy inefficiency, and complex maintenance requirements. The system incorporates high-efficiency particulate air (HEPA) filters, activated carbon filters, and ultrasonic humidification technology to effectively remove particulate matter, allergens, and airborne contaminants while simultaneously maintaining optimal humidity levels. A rechargeable lithium-ion battery was integrated to ensure portability, enabling users to use the PRA-PH without relying on a constant power source. Additionally, smart sensors and microcontroller-based control systems were employed to automate the device's operation, adjusting purification and humidification settings based on real-time air quality measurements. The PRA-PH was subjected to rigorous testing to evaluate its efficiency in purifying air and maintaining suitable humidity levels across various indoor environments. The results demonstrated significant improvements in air quality, showcasing the device's ability to effectively remove pollutants and maintain a comfortable humidity range. This study contributes to a portable and rechargeable air purifier and humidifier system that addresses the limitations of existing solutions. The PRA-PH's innovative design, efficient operation, and user-friendly interface make it a promising option for individuals seeking a convenient and effective way to improve indoor air quality and enhance the overall well-being of Ugandans.